Longitudinal Analysis of Short-term Changes in Relationship Conflict During COVID-19: A Risk and Resilience Perspective - Lee, Shawna J. (Journal of interpersonal violence, 2022)
This study uses a risk and resilience framework to examine short-term self-reported changes in relationship conflict early in the COVID-19 pandemic (March and April 2020). Longitudinal data from U.S. adults in a romantic relationship (N = 291) were collected via three waves of an online survey. Participants self-reported anxiety, depression, increased alcohol use, and dyadic coping since the pandemic. Relationship conflict variables included whether the participant reported that they and their partner ?had disagreements related to the Coronavirus,? ?had more disagreements than usual,? ?had more verbal fights than usual,? and ?had more physical fights than usual? in the past two weeks. Analyses controlled for sociodemographic characteristics as well as days spent in lockdown and employment change due to COVID-19. Results indicated that couples? disagreement and verbal fighting scores increased from Time 1 to Time 2, but disagreements related to COVID-19 and physical fighting did not. Couples with higher levels of dyadic coping reported fewer fights and disagreements on average. However, dyadic coping did not buffer participants from increases in relationship conflict. Increased alcohol use since the pandemic was positively associated with disagreements related to COVID-19, disagreement scores, and verbal fighting scores. More days spent in lockdown was associated with increases in disagreements related to COVID-19. The conditions created by COVID-19 may contribute to worsening relationship conflict, even among couples who start with high levels of dyadic coping. Depression and alcohol use may contribute to poorer relationship quality during the pandemic. There is need for enhanced intervention and mental health supports to mitigate the potential effects of the pandemic on couples? relationship functioning.